Synthesis of some substituted pyrimidines via cycloaddition reaction of amidines and chalcones - H. M. Al-Ajely; G. T. Sedeek; M. S. Al-Ajely (College of Education for Pure Sciences, 2009)
ABSTRACT Substituted amidines (1,2) where prepared from the condensation of benzyl, furfuryl alcohols and ethyl sulphate with thiourea. Chalcone compounds (3,5a and 5b) where also prepared from condensation of 4-nitrobenzaldehyde to give compound (3) while acetophenone, 4-hydroxy benzaldehyde and 1,3-dibromopropane gave the diformyl intermediate (4) then it was underwent further reaction with either acetophenone or 4-methyl acetophenone to afford compounds (5a,5b) respectively. Condensation of the above amidines with the resulted chalcones or dichalcones afforded the substituted pyrimidines (6-11). Their structures confirmation were studied by IR and were discussed.